ทัศนคติต่อผลกระทบสุขภาพเบื้องต้นจากการใช้สารเคมีป้องกันกำจัดศัตรูพืชในการปลูกพืชไร่ - ใจเตี้ย, สามารถ (Ganesha Journal, 2012)
[บทคัดย่อภาษาไทยไม่สมบูรณ์] The purpose of this research was to study attitude of pesticide usage in farm crops on health effect. Data was collected by using questionnaires, group discussion and in-depth interview. A sample group used for this research consisted of 142 farmers. Data were collected through used of descriptive statistics and qualitative data using content analysis. The results indicated that the relationship aspect of physical and mental health effect were high level (Mean=2.98±0.95 and 2.79±0.29), social and spiritual health effect were modulate level (Mean=1.67±0.69 and 2.17±0.68). However the farmer recommendations based on the biological that resolve the pest–controlling chemical and the departments to develop knowledge activities for farmers.